Development of method of use of acid-resistant selective action enzyme preparations - Шиян, Петро Леонідович; Мудрак, Тетяна Омелянівна; Куц, Анатолій Михайлович; Боярчук, Ярослав Андрійович (Eastern-European Journal of Enterprise Technologies, 2015)
A lot of studies were conducted nowadays in distilling industry on biocatalysis and fermentation of wort from starch-containing raw material using selective action enzyme complexes, but operational parameters for hydrolysis of starch-containing raw material biopolymers are not sufficiently investigated at low pH of the substrate. On the market of enzyme preparations in Ukraine there are acid-resistant enzymes that enable hydrolysis of grain mashes in low pH environment. This article concentrates on determination of efficiency of use of acid-resistant enzyme preparations (EP) when producing worts from starch-containing raw material. The results of studies on content in wort of water-soluble carbohydrates and insoluble starch depending on pH, temperature of termofermentive processing (TFP) and enzyme activity stabilizer Ca2+ ions are demonstrated. In terms of bioconversion efficiency of raw grain material components and assurance of microbiological purity of intermediate products of alcohol production, optimum pH is 3.8 - 4.0, mash processing time is 90 minutes.